The influence of service quality on Customer satisfaction of cordela iin hotel in bengkulu - Faradila Dwi Nanda; Sri Handayani; Rahman Febliansa (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
The aim of this research is to describe and analyze the influence of service quality on customer satisfaction at Cordela Inn Hotel Bengkulu. This type of research uses quantitative research methods. The sampling technique used a questionnaire of 75 respondents. Data analysis uses Multiple Linear Regression analysis. The results of the analysis show a significant positive influence on the variables Reliability, responsiveness, guarantee, empathy and physical evidence on customer satisfaction at Cordela Inn Hotel Bengkulu. Reliability (X1) on customer satisfaction at Cordela Inn Hotel Bengkulu because t count is greater than t table (3.990>1.666) with a significant value of 0.00 < 0.05. because t-count is greater than t-table and the significant value is 0.05, H0 is rejected and Ha is accepted, significantly positive between Responsiveness Variable X2 on customer satisfaction at Cordela Inn Hotel Bengkulu because t-count is smaller than t-table ( 3.181>1.666) with a significant value of 0.02 < 0.05. Because the value of t-count is greater than t-table and the significant value is 0.05 then H0 is rejected and Ha is accepted, Guarantee Variable with a significant value of 0.00< 0.05. Because the value of t- count is smaller than t-table and the significant value is 0.05, then H0 is rejected and Ha is accepted, Empathy with a significant value of 0.00 <0.05. Because the value of t- count is greater than t-table and the significant value is 0.05 then H0 is rejected and Ha is accepted, Physical Evidence with a significant value of 0.00<0.05. Because the value of t- count is greater than t-table and the significant value is 0.05, H0 is rejected and Ha is accepted.